2013
DOI: 10.1179/2046905513y.0000000104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particulate air pollution and passive smoking on surrogate biomarkers of endothelial dysfunction in healthy children

Abstract: The findings suggest that in healthy children PM concentration has a significant independent association with biomarkers of endothelial dysfunction and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Rodent studies suggest that increased exposure to air pollution may result in metabolic dysfunction and obesity via increased adipose tissue inflammation, hepatic lipid accumulation, and decreased glucose utilization in skeletal muscle (30,31). Prolonged exposure to combustion-related air pollutants may also increase oxidative stress and systemic inflammation, resulting in activation of stress kinases that lead to defective insulin receptor signaling that results in peripheral insulin resistance (30,32,33). Future studies should examine these outcomes in conjunction with systemic markers of inflammation in order to explore whether inflammatory processes mediate any of these observed relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent studies suggest that increased exposure to air pollution may result in metabolic dysfunction and obesity via increased adipose tissue inflammation, hepatic lipid accumulation, and decreased glucose utilization in skeletal muscle (30,31). Prolonged exposure to combustion-related air pollutants may also increase oxidative stress and systemic inflammation, resulting in activation of stress kinases that lead to defective insulin receptor signaling that results in peripheral insulin resistance (30,32,33). Future studies should examine these outcomes in conjunction with systemic markers of inflammation in order to explore whether inflammatory processes mediate any of these observed relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Children appear to be more vulnerable than adults to the adverse health effects of PM and other air pollutants because of their smaller airways and lung size, increased baseline ventilation rates, propensity to mouth breathe, and greater time spent running, jumping, and other aerobic play activities which expose them to greater pollutant loads penetrating deeper into lung tissues (Wright and Brunst, 2013; Bateson and Schwartz, 2008). It is indicative that higher exposure to urban air pollutants is associated with increased blood markers of oxidative stress, systemic inflammation, and endothelial dysfunction in children (Wu et al, 2015; Calderon-Garciduenas et al, 2009; Kelishadi et al, 2014; Poursafa et al, 2011). …”
Section: 0 Introductionmentioning
confidence: 99%
“…This, along with their smaller lung volumes, higher baseline ventilation rates, tendency to mouth breathe, and other attributes, can expose children to greater pollutant loads compared to older individuals [ 19 , 20 ]. Several authors have reported that higher exposure to urban air pollutants is associated with increased blood markers of oxidative stress, systemic inflammation, and endothelial dysfunction in children [ 5 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%